UTILIZING BRAINLY AS A SOCIAL QUESTION-AND-ANSWER (Q&A) SERVICE IN ENGLISH LEARNING MATERIALS: BENEFITS AND LIMITATIONS - Fitria, Tira Nur (Universitas Bunda Mulia, 2023)
This study describes Brainly as a social question-and-answer (Q&A) service in English learning and finds the positive and negative impacts on teachers and students. This research is descriptive qualitative. The analysis shows that using Brainly is easy. We can open Brainly at https://Brainly.co.id/. If we do not have an account, we can register using Gmail, then log in using the Brainly account. To make a question, click